Analisis Citraan Dalam Puisi â€˜Perempuan Yang Tergusurâ€™ Karya W.S. Rendra - Mochammad Dimas Adam Permana; Haerussaleh Haerussaleh; Nuril Huda (Estetik)
This research focuses on imagery in the poetry collection â€œPerempuan Yang Tergusurâ€ by W.S. Rendra. While the aim of this research is to describe the various types of imagery in the collection of poems â€œPerempuan Yang Tergusurâ€ by W.S. Rendra. The method used is descriptive qualitative method. While the type of research used is library research. The research data focused on written data regarding the imagery aspect contained in the collection of poems â€œPerempuan Yang Tergusurâ€ by W.S. Rendra. For data collection, the techniques used are reading techniques and note-taking techniques. The results of the analysis of the poetry of Perempuan Yang Digusur found 5 (five) forms of imagery, namely: (1) visual imagery; (2) auditory imagery; (3) olfactory imagery; (4) tactile imagery, and; (5) motion image. The imagery in the poem "â€œPerempuan Yang Tergusurâ€ is described by the character "you", namely "evicted women" which is a representation of reality that occurs in marginalized communities who live in various big cities with various kinds of suffering and various injustices that they experience